2009
DOI: 10.1089/dna.2008.0810
|View full text |Cite
|
Sign up to set email alerts
|

ACEVariants Interact with the RAS Pathway to Confer Risk and Protection against Type 2 Diabetic Nephropathy

Abstract: Genetic predisposition has been proposed to be a major determinant in the development of renal complications of diabetes. Among candidate genes examined for susceptibility to diabetic nephropathy, angiotensin-converting enzyme (ACE) gene has been found to be associated with pathogenesis and progression of diabetic nephropathy. However, the role of other renin-angiotensin system (RAS) polymorphisms and their possible interactions with different ACE I/D genotypes are less clearly defined. Recent studies also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 41 publications
3
46
0
3
Order By: Relevance
“…Therefore, we suggest that the genetic variation at the ACE locus as D/D variant in intron 16, contribute to an increased risk of nephropathy in T2DM patients, but not extent of DN severity (as the allelic or genotypic distribution was comparable between the two DN groups) in studied population. Our findings were in conformity with other studies [26][27][28][29][30][31] but not all [32,55,56]. This difference may possibly be due to different races, methods of quantitation and patient selection; as proteinuria in adults is a multifactorial condition frequently linked with diabetes, the issue of whether proteinuria is due to diabetes or some other etiology remains debatable, but there was no uncertainty in our group of patients on the role of T2DM in diabetic nephropathy constitution as we excluded the patients who had proteinuria/renal disorders before their diabetes was diagnosed, thus we confined our study to diabetic kidney diseases.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, we suggest that the genetic variation at the ACE locus as D/D variant in intron 16, contribute to an increased risk of nephropathy in T2DM patients, but not extent of DN severity (as the allelic or genotypic distribution was comparable between the two DN groups) in studied population. Our findings were in conformity with other studies [26][27][28][29][30][31] but not all [32,55,56]. This difference may possibly be due to different races, methods of quantitation and patient selection; as proteinuria in adults is a multifactorial condition frequently linked with diabetes, the issue of whether proteinuria is due to diabetes or some other etiology remains debatable, but there was no uncertainty in our group of patients on the role of T2DM in diabetic nephropathy constitution as we excluded the patients who had proteinuria/renal disorders before their diabetes was diagnosed, thus we confined our study to diabetic kidney diseases.…”
Section: Discussionsupporting
confidence: 94%
“…This polymorphism was associated with circulating ACE levels [23][24][25] and owing to its central role in the regulation of blood pressure, sodium metabolism and renal hemodynamics [16,17], it is reasonable to hypothesize that genetic variation of ACE I/D contributes to the development of DN and numerous studies have addressed the role of this polymorphism in the complex etiology of DN, albeit with conflicting results i.e. several studies have demonstrated [26][27][28][29][30][31] or refuted [32][33][34] the role of ACE D variant as candidates for the development of DN. The discrepant finding among studies is attributed to genetic and environmental heterogeneity among different populations.…”
Section: Introductionmentioning
confidence: 99%
“…In T2DM patients from Tehran the presence of the D allele of ACE was associated with higher ACE activity and increasing severity of albuminurea (11,20). Further, in Asian Indian and Tunisian patients with diabetic nephropathy the frequency of the D allele and the DD genotype was significantly increased compared with diabetic without nephropathy (21,22). In a metaanalysis by Staessen et al (23) it was reported that DD genotype of ACE I/D polymorphism versus II genotype is associated with 1.56-fold increased risk of diabetic nephropathy.…”
Section: Ace I/d Polymorphism: Onset and Progression Of Diabetic Nephmentioning
confidence: 89%
“…In the presence of AGT M235T gene polymorphism, elevated plasma AGT concentration is seen. 18,35 TT homozygote genotype results in the highest AGT elevation, which in turn increases angiotensin II level. 36 Such high angiotensin II levels may cause glomerular injury due to both systemic and glomerular pressure increase.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Therefore, the main genes whose DN associations are most commonly studied are angiotensinogen-converting enzyme, angiotensinogen (AGT), and angiotensin II Type 1 receptor genes, which code parts of the RAS system. 18 AGT M235T gene polymorphism in RAS is related to elevated AGT levels and hypertension. [19][20][21] Due to the association between this gene polymorphism and hypertension it has also been linked to DN.…”
Section: Introductionmentioning
confidence: 99%